A NEW SPECIES OF WATER SNAKE GENUS HYPSISCOPUS (SERPENTES: HOMALOPSIDAE) FROM SULAWESI, INDONESIA - Amir Hamidy; Quraisy Zakky; Nurul Fitriyana; Wempi Endarwin (BRIN Publishing (Penerbit BRIN), 2023)
We describe a new species of water snake genus Hypsiscopus that was formerly placed in the genus Enhydris from Towuti Lake, South Sulawesi, based on six specimens collected in 2003 and a specimen collected in 2019. The new species has several significant differences from other species in the genus Hypsiscopus (H. matannensis, H. plumbea, and H. murphyi) in possessing laterally compressed tail, higher number of scale rows in mid body, higher number of ventral scales, lower number of subcaudal scales, and distinct color pattern. The new species is likely distributed only in the Towuti Lake, and has higher level endemicity compared to H. matannensis. Further studies on the population and distribution are needed to evaluate its conservation status.